MODEL COOPERATIVE LEARNING TIPE TEAMS GAME TOURNAMENT (TGT), UPAYA UNTUK MENGEMBANGKAN KARAKTER KOMUNIKATIF SISWA - Ulfah, Mariah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
Writing this article is to describe the concept model of Cooperative Learning Type Teams Games Tournament (TGT) and describe its relationship with the increase in the development of students' communicative character. Model of Cooperative Learning Teams Type Game Tournament (TGT) is learning that utilizes small heterogeneous groups and allow students to work together to maximize their learning, involving the activities of all students without any differences in status, involving the role of students as peer tutors, and contains elements of the game in the tournament with using numbered cards and progress of individual scoring system, where students compete with other team members with the same level of academic ability in the tournament table, besides that there is reinforcement (reinforcement) at each end of the lesson in the form of an appreciation of the improvement results achieved by the students. In Cooperative Learning Type Teams Game Tournament comunity are learning concepts that will encourage students to work together and interact with each other. Elements of the game will create a fun learning environment, so that social interaction are good.